The simple economics of global fuel consumption - Doga Bilgin; Reinhard Ellwanger (Bank of Canada, 2019)
This paper presents a structural framework of the global oil market that relies on information on global fuel consumption to identify flow demand for oil. We show that under mild identifying assumptions, data on global fuel consumption help to provide comparatively sharp insights on elasticities and other key structural parameters of the global oil market. The estimated elasticity of global fuel demand in the short run with respect to crude oil prices is around -2 percent, which is considerably more inelastic than estimates of local fuel demand elasticities based on disaggregated data. Our framework is particularly suitable for understanding the evolution of quantities in the global oil market and provides new evidence on the magnitude of different types of oil price shocks and their macroeconomic and environmental impacts.
Keywords: C51; Q41; Q43; L71; 330; Economic models